PROTAC Bromodomain Inhibitor ARV-825 Displays Anti-Tumor Activity in Neuroblastoma by Repressing Expression of MYCN or c-Myc - Li, Zhiheng; Lim, Su Lin; Tao, Yanfang; Li, Xiaolu; Xie, Yi; Yang, Chun; Zhang, Zimu; Jiang, You; Zhang, Xianbing; Cao, Xu; Wang, Hairong; Qian, Guanghui; et al. (Frontiers in Oncology, 2020)
Neuroblastoma is the most common solid tumor in childhood. To date, targeting MYCN, a well-established driver gene in high-risk neuroblastoma (NB), is still challenging. In recent years, inhibition of bromodomain and extra terminal (BET) proteins showed great potential in multiple of Myc-driven tumors. ARV-825 is a novel BET inhibitor using proteolysis-targeting chimera (PROTAC) technology which degrades target proteins by the proteasome. In this study, we investigated the effect of ARV-825 in neuroblastoma in vitro and in vivo. Our results showed that ARV-825 treatment robustly induced proliferative suppression, cell cycle arrest, and apoptosis in NB cells. Moreover, ARV-825 efficiently depleted BET protein expression, subsequently repressing the expression of MYCN/c-Myc. In the NB xenograft model, ARV-825 profoundly reduced tumor growth and led to the downregulation of BRD4 and MYCN expression in mice. Taken together, these findings provide evidence that PROTAC BET inhibitor is an efficient way to achieve MYCN/c-Myc manipulation, and ARV-825 can be used as a potential therapeutic strategy for the treatment of neuroblastoma.